Learning butch: Tracing lesbian and trans becoming in the classroom - Helton, L. (Journal of Lesbian Studies, 2022)
In this autobiographical essay, I study the ways in which becoming a classroom teacher illuminated the school-based gender socialization that had shaped my contested understanding of myself as a girl and woman. Leaning on the work of queer theorists both within and outside of fields explicitly marked as “pedagogical,” I examine the notion of the “hidden curriculum” of gender as made manifest in my first years teaching middle school English, and the transformative capacity within my students—and the learning spaces I shared with them—to deconstruct, play with, and disrupt, if not unlearn, the gender “scripts” that had bound us to the failing coda of identification linked to larger systems of oppression which the institution of school reifies. Tracing my developing self-identification as a lesbian alongside my years of feeling “just outside” of the archetype of the professional woman teacher, I explore the possibilities for the secondary classroom to playfully and rigorously trouble normative modes of categorization and identification, broadening our understanding of who school “works” for.
Keywords: approches et analyses; identités LGBTQIA2+; personnes trans*; pédagogie; queer; ressource en ligne; thématiques